An Automated Device for Recording Peripheral Arterial Waveform - Tuukka Panula; Juuso Blomster; Mikko Pänkäälä; Tero Koivisto; Matti Kaisti (United States, 2025)
The aim of the study was to develop an automated device for recording peripheral arterial pulse wave, in order to assess cardiovascular health. Recent studies have shown that photoplethysmography (PPG) is a viable technique to measure peripheral pressure waveform. We developed a small motorized device that can measure pulse waveform from a finger. The device targets the distal transverse palmar arch (DTPA) artery using infrared wavelength PPG. Measurements were taken from healthy subjects (n = 8).The device was validated by performing HR detection and waveform analysis. The device was able to record high quality blood pressure calibrated arterial waveforms and detect beat-to-beat heart rate allowing the assessment of cardiovascular health status.
CinC 2019